PELATIHAN PUBLIC SPEAKING DALAM MENINGKATKAN KEPERCAYAAN DIRI SISWA PKBM BAKTI ASIH CILEDUG TANGERANG - Jeanie Annissa; Ricky Widyananda Putra (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Communication activities can be broadly divided into two main streams, namely verbal communication and nonverbal communication. Verbal communication can be broadly defined as communication using spoken language as the medium. Meanwhile, nonverbal communication is communication that uses nonverbal means as the implementing medium. These things, cannot be judged as something of a deficiency or especially a weakness because perhaps their need to behave in this way still dominates the whole of their life and behavior. Verbal communication, in this case related to speech, does not arise from a vacuum. He exists because there is a response from the situation that surrounds him. Literally speaking in public is an ability to survive because development and progress in social life or the work environment is greatly influenced by our ability to speak effectively. Apart from the aforementioned matters, this speaking skill is very sustainable with the culture in Indonesia because Indonesian people tend to have a stronger verbal tradition than the writing tradition. It would be nice if their energy was directed towards mastering public speaking. In the public speaking method, it allows learners to be able to expose all of their abilities in speaking. But more than that, learners will learn how to cultivate a sense of confidence in themselves. They must be able to master their fear and their shame in front of a large audience. The subject of community service is a community consisting of teenagers, fathers, mothers who are members of PKBM Bakti Asih, Jl. Raya Raden Fatah No. 7 Sudimara Barat, Ciledug-Tangerang. The reason for choosing this institution is because PKBM Bakti Asih is a package A, B and C educational institution that is currently developing in Tangerang City, besides that the institution is open to universal science studies. It is hoped that with this community service activity, which contains some communication materials and media understanding that relies on the public speaking method, it will raise awareness that public speaking can increase self-confidence in an individual. Keywords: Communication, Public Speaking, Confidence